Contrasting population-level responses to Pleistocene climatic oscillations in an alpine bat revealed by complete mitochondrial genomes and evolutionary history inference - Alberdi, A.; Gilbert, Thomas; Razgour, O.; Aizpurua, O.; Aihartza, J.; Garin, I. (Blackwell Publishing, 2015)
Aim We used an integrative approach to reconstruct the evolutionary history of the alpine long-eared bat, Plecotus macrobullaris, to test whether the variable effects of Pleistocene climatic oscillations across geographical regions led to contrasting population-level demographic histories within a single species. Location The Western Palaearctic. Methods We sequenced the complete mitochondrial genomes of 57 individuals from across the distribution of the species. The analysis integrated ecological niche modelling (ENM), approximate Bayesian computation (ABC), measures of genetic diversity and Bayesian phylogenetic methods. Results We identified two deep lineages: a western lineage, restricted to the Pyrenees and the Alps, and an eastern lineage, which expanded across the mountain ranges east of the Dinarides (Croatia). ENM projections of past conditions predicted that climatic suitability was reduced during cold stages in the areas inhabited by the western lineage, while the opposite trend was observed in the mountains inhabited by the eastern lineage. The palaeodemographic scenario that best fitted our data is consistent with the western lineage population size having shrunk repeatedly because of the extensive glaciation events that occurred in the Alps and Pyrenees during the Pleistocene. In contrast, the eastern lineage maintained a constant population size as is consistent with more limited glaciation in the mountains of south-eastern Europe and the Middle East. Main conclusions This study shows that the demographic response of populations to Pleistocene climatic oscillations depended on their geographical location, offering an example of population-level variations in the effects and longterm consequences of climate change.